(untitled) (mathematica didactica, 2021)
In many universities, mathematics students are requested to hand-in weekly assignments and receive a certain grading. This duty is questioned sometimes, e.g. due to the high demand of grading time. At a German University, such a duty was newly introduced in a first-semester lecture for students training to be mathematics teachers on all school forms in the winter semester 2018/19. This paper documents a substantially higher participation in the final exam as well as better success rates. Further, results of a student survey show a high acceptance and positive evaluation of the newly introduced duty. We discuss to what extent this provides evidence for a positive effect of this duty.